(untitled) - Kenkel, Cindy S. (Boston, 2007)
Extreme Résumé Makeover focuses on the written communication involved in finding a job, including résumés, cover letters, and thank you notes. “Before and after” examples of real résumés are incorporated providing concrete visual examples to use as models for the final product. Each resume example indicates the errors in the initial attempt and suggested improvements. There are also sections on electronic formatting and electronic résumés, as well as lists of key words for various careers
Keywords: Résumés (Employment),College students,College graduates,Sinh viên đại học,Sinh viên tốt nghiệp đại học; Employment,Employment,Việc làm,Việc làm